GAME EDUKASI PADA PEMBELAJARAN MATEMATIKA: TANGGAPAN SISWA SMP BERDASARKAN GENDER - Salsabila, Nilza Humaira; Lu'luilmaknun, Ulfa; Novitasari, Dwi; Tyaningsih, Ratna Yulis; Ardani, Riska Ayu (Jurusan Pendidikan Matematika Universitas Borneo Tarakan, 2020)
AbstractThe use of media in mathematics learning can help students to learn more easily. One of them is educational game media. The study aims to describe the responses of junior high school students based on gender to learn mathematics by using educational game media. The subjects of this study were 7thand 8thgrade of junior high school students in Mataram-West Nusa Tenggara, a total of 101 students. Study data were obtained from a questionnaire about the use of educational games in mathematics classes. Study data processing using descriptive statistics, qualitative methods. The results of the study show that there are differences in responses between male and female students, towards: fun learning and increased motivation using media games and missions in educational games.Keywords: Edukasi, Game, Gender, MathematicsAbstrakPenggunaan media pada pembelajaran matematika dapat membantu siswa untuk lebih mudah belajar. Salah satunya media game edukasi. Adapun studi ini bertujuan untuk mendeskripsikan tanggapan siswa SMP berdasarkan gender terhadap pembelajaran matematika dengan menggunakan media game edukasi. Subjek penelitianini adalah siswaSMP kelas 7 dan 8 di Mataram-Nusa Tenggara Barat sebanyak 101 siswa. Data studi diperoleh dari kuesioner tentang penggunaan game edukasi di kelas matematika.Pengolahan data studi menggunakan statistic deskriptif ,metode kualitatif. Hasil studi menunjukkan bahwa terdapat perbedaan tanggapan antara siswa laki-laki dan perempuan, terkait: pembelajaran yang menyenangkan dan motivasi yang meningkatdenganmenggunakan media game, serta misi pada game edukasi.Kata kunci: Education, Game, Gender, Matematika